Literature as a factor in education - Correll, Maggie (My University, 1897)
Introduction: In order to think of anyone of the factors of an education, as related to all others, we must have for a foundation a definite understanding of the end to be sought, and the benefit to be derived therefore. In general we understand education to be a process of development of the intellectual faculties; an unfolding of the latent capabilities of an individual; the bringing out and learning to know, and the development of the true self. This true self Mr. Heiram Carson in his “Aims of Literary Study” talks: of as an inmost being, a very small part of which we can ever become conscious of in this life; but which is influenced in its development by our thoughts and actions, and in turn prompts our thoughts, directs our actions, and guides our lives here, and determines our course in the great eternity which follows, along the line of its greatest development.
Citation: Correll, Maggie. Literature as a factor in education. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Literature; English; Education; College; Theses; Manuscripts (documents)